The impact of learning at UST Medical School skill laboratory on 3rd & 4th year medical students' competencies of clinical skills - Dawood A. Alhidabi; Inas Alsheekh; Iqbal Ali Rabbad; Mahmoud Al-Hammadi; Raid Faisal Al-Baghdadi (University of Science and Technology, Yemen, 2010)
A Total of 155 consenting year 3 and 4 medical students. The participants completed questionnaire listing 30 clinical skills divided into five groups. Students were asked to assess their clinical skills on a 1-5 scale, and we compared the assessment scores with students self-assessment. The current study was carried out only to investigate whether students mastered or performed skills during their training at skills laboratory or to study both the quality and quantity of skills performed during their training at skill laboratory(i.e amount of feedback students receive), (Other instruments must be used, such as check list). Intensive small group skills training programme offered in year 2-4 medical students at skills laboratories. Results in this study showed that student's self- evaluation had highly significant correlation with those of their skills exams in medical skills laboratory with P value 0.0001. Mastered medical skills among these students had significantly high. Students had higher scores in some groups of skills, which can be explained by better organization of clinical skills teaching in these subjects, or by higher student interest in these skills. Also, there was no significant difference in mean between males and females in musculoskeletal skills, cardiovascular skills and hepatobilliary skills (p value >0.05), but in other subjects(mastering respiratory skills, mastering GIT skills) there is higher means in females than males and this difference is significant( p value <0.05). female students had higher scores in GIT, respiratory system and probably because they were more inclined to these specific skills. Conclusion: Students self- assessed level clinical skills was correlate with their assessment scores. And clinical skills training at skills laboratory has additional positive influence on students self-assessed level of clinical skills. Training in a skills laboratory appear to result in students performing more skills during clerkships.